Prognostic value of morphologic and clinical Pparameters in pT2 - pT3 prostate cancer - Almeida, Jose C. (2007)
OBJECTIVES: Verify the efficacy of clinical and morphologic parameters currently applied, including an immunohistochemical panel, in the prognostic of prostate cancer, in specific stages of the disease. MATERIALS AND METHODS: In the period from 2002 to 2005, 40 surgical specimens were selected from patients submitted to radical prostatectomy, with their respective diagnostic biopsies. Based on the pathological stage pT2 or pT3, the specimens were separated into two groups, each one with 20 specimens. The results were confronted with pre- and postoperative clinical data. Between the groups studied, the following was also analyzed: the profile of the expression of molecular markers such as PSA, E-caderin, chromogranin-A, synaptofisin, P53 and Ki-67, both in the material coming from the prostatic biopsy and from the surgical specimens of all patients. RESULTS: Data showed that patients with prostate-confined disease (pT2) presented lower PSA and Gleason score rates, in relation to the group with extra-prostatic disease (pT3). Quantitative measures obtained for the percentage of positive fragments from the biopsy revealed that patients from the pT2 group presented a lower mean percentage when compared to the pT3 group. Positive margins of both groups influenced the need for complementary treatment before biochemical progression. The comparison of the molecular marker expression in both stages was not significantly different. CONCLUSION: It is evident the need to improve new methods, predominantly morphologic and molecular, that are able to further exploit the study of the material from the prostatic biopsy. As to the profile of the molecular markers used in both studied groups, there was no significant difference in the sense of outlining an additional prognostic factor in the clinical practice.